DETERMINANTS OF FINANCIAL PLANNING: A META-ANALYSIS ON THE EFFECTS OF FINANCIAL LITERACY AND INCOME - Daffa Eka Septianda; Clarashinta Canggih (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This meta-analytic study aims to synthesize empirical evidence on the influence of financial literacy and income on financial planning, addressing inconsistent findings in previous literature. Design/Methodology/Approach: Employing a quantitative meta-analysis approach following PRISMA guidelines, this study analyzed secondary data from primary empirical studies published between 2021 and 2026. A systematic search across Scopus and Google Scholar yielded k = 11 eligible studies. A random-effects model was applied to account for expected methodological and demographic heterogeneity. Findings: The pooled effect sizes indicate that both financial literacy (r = 0.460, p = .065) and income level (r = 0.452, p = .268) show moderate effect sizes but do not reach statistical significance. Significant heterogeneity was observed in both analyses (Financial Literacy: Q(6) = 50.91, p < .001; Income: Q(3) = 38.75, p < .001), suggesting the presence of potential moderating variables. Novelty: This study provides a novel behavioral finance perspective by explaining the "knowledge-behavior gap" and the "income-saving paradox," moving beyond traditional rational-choice assumptions. Practical/Theoretical Implications: Theoretically, it integrates the Life-Cycle Hypothesis with behavioral biases (e.g., overconfidence, lifestyle inflation). Managerially, it implies that financial education must transcend knowledge transfer to include behavioral nudges, while policymakers must design inclusive financial products that accommodate varying income trajectories.